EFEKTIFITAS PEMBELAJARAN GERAK DASAR LEMPAR DENGAN PENDEKATAN BERMAIN PADA PESERTA DIDIK KELAS III SEKOLAH DASAR - Mashud Mashud (Lambung Mangkurat University, 2014)
The Learning Effectiveness Of Basic Throwing Movement Through Playing Approach On Third Grade Of Elementary School. This research aims to produce learning effectiveness of basic throwing motion. The study was conducted by involving research subjects namely physical education teachers and third grade students of SDN Loktabat 7. This Research uses classroom action research method (action research) which has several phases of research steps including: planning, action, observation and reflection. Data collected include qualitative, in the form of responses observer/associate teacher namely criticism, suggestions, comments both orally and in writing using interview techniques, discussion, documentation and questionnaires and quantitative data in the form scale of ordinal numbers.Data collected during the study is data about learning feasibility and effectiveness of learners. Before the action research was done, effectiveness of student learning outcomes in the form of concept understanding of basic throwing movement and throwing ability showed that there were 16 students (45,71%) got standard grade. After action research was conducted, students who pass the study increased to 22 ( 62.86 % ) in the first cycle , 26 students (80%) in the second cycle, and 33 students (94.29 %) in the third cycle . Before the action research was done, learning mastery of the students classically was 45.71 %. But after the action research was conducted, it has increased 17.15 % to 62.86 % in cycle I. In the second cycle it has increased by 11.43 % to 74.29 %, while the third cycle, it has increased 20 % to94.29%. While the study results of the learning feasibility showed that the playing activity can be done well proven by the high students’ involvement and participation in learning, but teachers should have more control of the movement preciousness done by the students, because it is feared the students focus only to playing activity and they forget the right technique of basic throwing movement.Overall, research phasing from the first until third cycle undergo the improving results, both of the effectiveness and feceability of learning basic throwing movement. Keywords: Learning effectiveness, basic throwing movement, playing approach